Base-catalyzed oxidation of poly (ethylene glycol) by alkaline permanganate: Part I. Kinetics and mechanism of formation of coordination intermediate complex - Refat M. Hassan; Suzan A. Sayed; Samia M. Ibrahim (Egyptian Journal of Petroleum)
A spectrophotometric investigation has been applied to study the kinetics of oxidation of poly (ethylene glycol) (PEG) as a synthetic polymer by alkaline permanganate at a constant ionic strength of 1.0 mol.dm−3. The reaction was found to proceed through two distinct measurable stages. The first stage was relatively fast and corresponding to the formation of coordination polymer intermediate complexes involving blue hypomanganate (V) and/or green manganate (VI) transient species. The influence of variable factors on the oxidation rates such as the concentration of permanganate ion and PEG substrate concentrations as well as the pH and ionic strength have been examined. Under the pseudo-first-order reaction conditions of [PEG] ≫ [MnO4−], the experimental results showed a first-order dependence in [MnO4−] and fractional first-order kinetics in each of [PEG] and alkali concentration. The oxidation process was of base-catalyzed nature where the oxidation rates were increased with increasing the alkali concentration. The observed first-order rate constant was found to be 1.1 ×10−3 s−1 with deprotonation constant of 0.72 dm3 mol−1 at 45 °C. Blue hypomanganate (V) was detected for the first time by using a conventional spectrophotometer. The oxidation process has proceeded without the intervention of a free-radical mechanism. Colloidal manganese (IV) and the acid derivatives of PEG were identified as final oxidation products. The activation parameters of the second-order reaction have been calculated and found to be ΔH≠ = 40.66 kJmol−1; ΔS≠ = − 145.41 Jmol−K−1 and ΔG≠ = 83.99 kJmol−1. A plausible reaction mechanism for oxidation based on the evaluated activation parameters and in good consistent with the observed kinetic data was suggested and discussed.